Pemanfaatan Campuran Pati Singkong Dan Pati Ubi Jalar Sebagai Bahan Baku Pembuatan Plastik Biodegradasi - Agustina, Mistiyawati Eka; Arlianti, Lily; Nurlatifah, Ismi (Universitas Islam Syekh Yusuf Tangerang, 2024)
Plastic waste is already polluting the environment both land and oceans, as plastic consumption continues to increase. Biodegradable plastics are an effort to reduce environmental pollution, biodegradation plastics are plastics made from natural materials usually biodegradable plastics made from natural starch. Cassava starch is the most widely used type of starch and is developed for the manufacture of biodegradable plastics, and sweet potatoes are tubers whose starch content is quite numerous even though it has not been widely developed into plastic material. This research aims to produce natural plastics that can replace conventional plastics and reduce environmental pollution due to plastic waste. The study was conducted with variations in the composition of starch mixtures (50:0 gr, 35:15 gr, 25:25 gr, 15:35 gr, 0:50 gr) and variations in drying temperatures (40°C, 50°C, 60°C).In this study carried out organoleptic test, thickness value test, water absorption value test and degradation test. The results of this study showed biodegradable plastics that have the best characteristics are in the variation of the composition of the mixture 50:0 gr at a drying temperature of 60°C, with a thickness value of 0.11 mm and a water absorption value of 36.5%, but the rate of degradation in this variation is very slow